IMPACT OF SENSORY MARKETING ON CONSUMER BEHAVIOR (Heritage, 2020)
When making purchase decisions, consumers rely more on their emotions than on their minds. The senses allow people to connect with the world around them, but also to fully experience brands and to make consumers emotionally connected to them. The field of marketing, which deals with the study and use of human senses in branding, is known in the literature as sensory marketing. Today, it is necessary to offer consumers a full experience through brands through all five human senses. Only in this way companies can compete with their competitors in the market and accurately respond to the needs and desires of consumers. This paper explores the effects of sensory marketing methods on consumers. The main aim of this paper is to draw the attention of marketers to the possibilities of these methods to create an emotional connection between consumers and brands.
Keywords: Sensory marketing, human senses, brands, consumers